The influence of various anesthetic thechniques on life quality of patients during the postoperative period after curettage of the uterine cavity - Georgiyants, Marine; Dotsevych, Tamiliia; Vуsotska, Olena; Yurchenko, Olha (ScienceRise: Medical Science, 2019)
Curettage of uterine cavity (CUC) is an informative diagnostic and treatment method, which is widely applied in gynecology of one day. However, its low injury rate is not able to exclude completely the development of postsurgical pain syndrome, consequently changing the life quality of patients. The occurrence of psychosomatic effects is influenced by the underlying disease, concerning which the manipulation was performed, the psycho-emotional atmosphere of the hospital, the intensity of the pain syndrome, etc. Objective: to define the range of clinically significant changes of life quality after outpatient endouteral operational interventions, and to evaluate the influence of components of anesthesia service, which have the greatest influence on changing life quality of female patients in the early postoperative period. Materials and methods: during the postoperative period the interviewing of patients was conducted with the use of scale enquirer of life quality EQ-5D, “Enquirer of life quality of patients during the postoperative period” and with the use of visual analogue scale (VAS), statistical processing of received data was also performed. Results: the conducted research identified prime factors of influence over life quality of patient in pre- and postoperative period of CUC, rational methods of improving life quality after CUC. These are physical (postoperative pain syndrome) and psychological (fear of future surgery, nervousness regarding its carrying-out, its results and expectation of pain during operative intervention) factors. Conclusions: the prime factor, which has notional influence on life quality in the postoperative period of CUC, is a disorder of emotional-volitional sphere, albeit in imperceptible intensity, however in statistically significant feeling jittery and mental depression, caused by fear of women before the upcoming operational intervention, peculiarities of its performance and results, as well as the quality of anesthesia service. In the postoperative period of CUC the greatest influence on life quality of patients has the postsurgical pain syndrome. A method of preventive intraoperative anesthesia allows to prevent the development of pain syndrome in an efficient and timely manner, and thus goes into efficient way of improving life quality of patients of gynecologic hospital of one day in the postoperative period of endouteral operational interventions. Research results have also found out a circumstantial positive influence of the indicated method of anesthesia on the characteristics of emotional state and a possibility to prevent disorders in emotional-volitional sphere of female patients